Prenatal Hypoxia and Placental Oxidative Stress: Insights from Animal Models to Clinical Evidences - Serena Silvestro; Valeria Calcaterra; Gloria Pelizzo; Placido Bramanti; Emanuela Mazzon (MDPI AG, 2020)
Hypoxia is a common form of intrauterine stress characterized by exposure to low oxygen concentrations. Gestational hypoxia is associated with the generation of reactive oxygen species. Increase in oxidative stress is responsible for damage to proteins, lipids and DNA with consequent impairment of normal cellular functions. The purpose of this review is to propose a summary of preclinical and clinical evidences designed to outline the correlation between fetal hypoxia and oxidative stress. The results of the studies described show that increases of oxidative stress in the placenta is responsible for changes in fetal development. Specifically, oxidative stress plays a key role in vascular, cardiac and neurological disease and reproductive function dysfunctions. Moreover, the different finding suggests that the prenatal hypoxia-induced oxidative stress is associated with pregnancy complications, responsible for changes in fetal programming. In this way, fetal hypoxia predisposes the offspring to congenital anomalies and chronic diseases in future life. Several antioxidant agents, such as melatonin, erythropoietin, vitamin C, resveratrol and hydrogen, shown potential protective effects in prenatal hypoxia. However, future investigations will be needed to allow the implementation of these antioxidants in clinical practice for the promotion of health in early intrauterine life, in fetuses and children.